CHANGING GLOBAL SCENARIO OF RESEARCH ON DISTANCE EDUCATION : A BIBLIOMETRIC ANALYSIS - Suriya, M. (Malaysian Journal of Library and Information Science, 1998)
Analysis of research trends on distance education (DE) covering 10 subject areas; Concepts and theories; Areas of applications; Levels of applications; Special learner groups; Methods of teaching; Psychology of learning; Support services; Course development; Choice of medium and Economics of management. The contribution of papers on these areas was on an upward trend at varying rate of growth. The highest publication rate is found on the medium of delivering the programmes (52 papers per annum). It is estimated that this field would grow to a total of 656 papers per annum in the year 2005. Profile of regions indicate that the European countries accounted for 40% of total research productivity on DE, followed by North and South America (23%), Asia (18%), Oceania (16%) and Africa (3%). It is estimated that the publication of Europe would be 941 by the year 2005, followed by Asia (937), America (580), Oceania (501) and Africa (90). The pattern of research publication is found to be uniform with each region concentrating on definite areas of research.